The Impact of Animated Videos on Student Awareness of Bullying - Baharuddin Condeng; Mohammad Novrian Hasanuddin; Azizah Saleh (Journal of Public Health and Pharmacy, 2025)
Introduction: Bullying among teenagers is a pervasive issue with significant physical, mental, verbal, and psychological repercussions. Effective health education methods that captivate students' attention are essential for addressing such detrimental behaviours. This study assesses the effectiveness of animated videos as a tool to enhance high school students' understanding of bullying, using a case study from Karya Bakti Mamboro High School. The dynamic and visually engaging nature of animated videos offers a promising avenue for improving educational outcomes. Methods: A pre-experimental design was adopted, involving 31 students from Karya Bakti High School. Data collection was performed using identity forms and pre- and post-intervention questionnaires. The impact of the animated video intervention was evaluated through Univariate and Bivariate analysis. Results: The intervention significantly improved the students’ knowledge about bullying. Initially, 54.8% of students were in the "poor" knowledge category, which decreased to 58.1% achieving "sufficient" knowledge post-intervention. The paired t-test revealed a significant increase in the average knowledge scores from 52.58 to 75.16 post-intervention (Sig. (2-tailed) = 0.000). Conclusion: Animated videos significantly enhance the understanding of bullying among high school students. This educational strategy not only improves knowledge but also engages students more effectively than traditional methods. The broader implications of this study suggest that incorporating such dynamic visual content into school curriculums or anti-bullying programs can play a critical role in mitigating bullying behavior. This method could potentially transform health education approaches, fostering a more interactive and impactful learning environment.